Dobra Nowina w środkach społecznego przekazu pod red. Henryka Sławińskiego, Ancilla Verbi, t. 10, Kraków 2020 - Kalbarczyk, Adam (Poznańskie Studia Teologiczne, 2021)
The Church must tirelessly seek appropriate means and language to effectively proclaim every person’s universal vocation to salvation. Today’s witnesses to the Gospel should use the potential of old and new means of communication in preaching and ministry. Above all, they should revive in themselves the courage to settle on ‘new areopaguses’. The most important goal of evangelization is to bring every person to an encounter with Christ, who is the main content of the proclaimed Good News. The authors of this monograph did not forget about it. By showing both the enormous possibilities and certain limitations of the new media in proclaiming the Gospel to the world, they first asked themselves whether those countless texts, images and sounds that fill today’s periodicals, radio, television, film truly reflect the face of Christ and let His voice be heard.